2007
DOI: 10.1111/j.1472-765x.2007.02275.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of extended-spectrum β-lactamase-producing Klebsiella pneumoniae in effluents and sludge of a hospital sewage treatment plant

Abstract: Aims:  To detect ESBL (extended‐spectrum β‐lactamase)‐producing Klebsiella pneumoniae present in the effluents and sludge of a hospital sewage treatment plant, evaluating the treatment plant’s potential to remove these micro‐organisms. Methods and Results:  Twenty samples (crude sewage, UASB reactor effluent, filtered effluent and sludge) were collected in the period from May to December 2006, in order to analyse antimicrobial susceptibility and to check ESBL production, the disc‐diffusion and the combined dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
58
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 25 publications
2
58
0
6
Order By: Relevance
“…ESBL-producing organisms have been emerging both in nosocomial and in community settings since the 1980s (4,13,14). In aquatic environments, ESBL-producing bacteria have been found in sewage and water samples (11,13,16), but their diversity in sediment habitats has never been analyzed before. In the present study, the diversity of ESBL-producing organisms was studied by both culture-dependent and culture-independent methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ESBL-producing organisms have been emerging both in nosocomial and in community settings since the 1980s (4,13,14). In aquatic environments, ESBL-producing bacteria have been found in sewage and water samples (11,13,16), but their diversity in sediment habitats has never been analyzed before. In the present study, the diversity of ESBL-producing organisms was studied by both culture-dependent and culture-independent methods.…”
mentioning
confidence: 99%
“…ARB in rivers may originate from anthropogenic sources, such as hospital, municipal, and aquaculture effluents (3,16,23); in addition, they could occur naturally, since many acquired resistance mechanisms originated in producers of antibiotics, such as actinomycetes (12). Both anthropogenic and naturally occurring ARB in water environments may compromise human health, since people may be infected by ARB through drinking water, aquatic products, and direct contact with water bodies.…”
mentioning
confidence: 99%
“…Although many resistant bacteria have been isolated from environmental samples, there are only limited studies that have addressed the detection of ESBL-producing bacteria from these types of samples [18,19]. Prado et al [19] observed the presence of Klebsiella pneumoniae producing ESBL in the effluent and sludge of hospital sewage plants.…”
Section: Introductionmentioning
confidence: 99%
“…Prado et al [19] observed the presence of Klebsiella pneumoniae producing ESBL in the effluent and sludge of hospital sewage plants. Therefore, the hospital sewage or the low efficacy of hospital sewage-treatment plants could result in the dissemination of ESBL-producing bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics are major contaminants found in polluted waters [13] and appear to play a significant role in the natural selection and survival of resistant strains. Antibiotic-resistant bacteria are also reported to be introduced to water bodies through waste discharges from animal husbandry and hospitals [14,15]. Estuarine environments are receptacles for various kinds of wastes draining into the system, which is highly favourable for horizontal gene transfer among pathogenic and non-pathogenic bacterial strains.…”
Section: Introductionmentioning
confidence: 99%